Working and Homeless: Exploring the Interaction of Housing and Labour Market Insecurity. Issue 1 (30th October 2019) - Jones, Katy; Ahmed, Anya; Madoc-Jones, Iolo; Gibbons, Andrea; Rogers, Michaela; Wilding, Mark
Abstract : Alongside an increasing focus on 'prevention', moving homeless adults into work is frequently considered an important part of helping them overcome homelessness and sustain an 'independent' life. However, a growing evidence base shows that work does not always offer the means to escape poverty, and many in employment face housing insecurity. Relatedly, there is increasing concern about the phenomenon of 'in-work homelessness'. Drawing on new data from a study of people's experience of homelessness in Wales, this article considers the hitherto underexplored topic of being both in work and homeless. The article provides a critical examination of how homelessness policy operates in practice, through presenting evidence of the experiences of a marginalised group (namely, working homeless people as users of homelessness services). It also considers how policy and practice could be modified to improve outcomes for homeless people and how prevention could play out in other contexts and welfare regimes.